Natural variation of CTS1 confers cold tolerance and blast resistance in rice - Wei Ye; Wendong Ma; Yingxiu Li; Zhenhua Guo; Shilei Gao; Haifeng Guo; Zezhong Yan; Sijing Shi; Shichen Han; Qijin Lou; Jin Li; Yunsong Gu; et al. (Proceedings of the National Academy of Sciences, 2026)
Improving multistress resilience in crops is essential for sustainable agriculture, yet the genetic mechanisms coordinating abiotic and biotic stress responses remain poorly understood. This study identifies CTS1 ( Cold Tolerance at the Seedling stage1 ), encoding the transcription factor OsWRKY74, as a key pleiotropic regulator that mediates both cold tolerance and blast resistance in rice. Through genome-wide association study, we found that CTS1 negatively regulates cold tolerance at the seedling stage. The natural allele CTS1 Hap1 confers greater cold tolerance than CTS1 Hap2 by mildly repressing the expression of CTB2 , thereby maintaining sterol glycoside homeostasis and membrane stability. Furthermore, during Magnaporthe oryzae infection, CTS1 activates the expression of OsHSP90 and upregulates pathogenesis-related genes, thereby enhancing blast resistance. Our findings reveal a dual-function mechanism of CTS1 in stress adaptation and provide valuable alleles for breeding multistress resilient rice varieties.